Agenesis of the Maxillary First Permanent Molars: A Clinical and Radiographic Evaluation of a Rare Case - Mallineni, Sreekanth Kumar; Maohmmad, Azher Mohiuddin; Patil, Anil Kumar; Kodali, Ranvitha Priya (UI Scholars Hub, 2017)
Congenitally missing first permanent maxillary molars is a rare finding in any given population. The reported prevalence rate of maxillary first molar agenesis ranges from 0.2 to 1.5%. The exact aetiology of this dental anomaly is not clearly documented. Generally, it can occur in association with other dental disturbances. The purpose of this article is to describe the clinical and radiographic evaluation of a case with bilateral congenitally missing first permanent molars and its association with dental anomalies such as microdontia and hypodontia.